2009
DOI: 10.1007/s10384-009-0677-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of higher order aberrations on contrast sensitivity function in myopic eyes

Abstract: Spherical and fourth-order aberrations significantly affect CSF in myopic eyes. However, the effect of myopia on CSF cannot be attributed only to HOAs. Other factors such as neural elements in the visual pathway should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Still, studies have successfully correlated specific visual complaints such as halos, glare, and contrast sensitivity with higher-order aberrations. 12 Further investigation of visual outcomes between the two laser platforms should be investigated before determining superiority in terms of visual image and quality postoperatively. Additional factors such as cost, availability, patient characteristics, and surgeon preference should be taken into consideration when determining the most appropriate laser to use for refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Still, studies have successfully correlated specific visual complaints such as halos, glare, and contrast sensitivity with higher-order aberrations. 12 Further investigation of visual outcomes between the two laser platforms should be investigated before determining superiority in terms of visual image and quality postoperatively. Additional factors such as cost, availability, patient characteristics, and surgeon preference should be taken into consideration when determining the most appropriate laser to use for refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“… [20] Feizi et al demonstrated that the AULSCF was significantly associated with total HOAs and fourth-order aberrations, but not third-order aberrations, in myopic eyes. [21] Fujikado et al found a significant association between the AULCSF and HOAs in eyes with cataract. [17] Although we cannot fully explain the discrepancy between the current and previous findings, the sample size, the methodology of the measurements, the distribution of subject age, the presence of age-related cataract, and other subject backgrounds of the study population, may contribute to this discrepancy.…”
Section: Discussionmentioning
confidence: 97%
“… [18] To date, there have been several studies assessing the effect of HOAs on the contrast sensitivity function in normal and diseased eyes. [17] [21] Liang et al showed that human eye aberrations play a crucial role in degrading retinal image quality. [19] Oshika et al reported that the AULCSF was significantly correlated with coma-like aberrations, but not spherical-like aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…26 Williams et al 27 argue that CSF is improved when most WAs are reduced with a deformable mirror or adaptive optics (AO) system, compared to when only defocus and astigmatism (LOAs) are corrected. Feizi and Karimian 28 investigated the relationship between HOAs and CSF in 70 myopic eyes. The 'Area Under The Log Contrast Sensitivity Function' (AULCSF) was calculated for all 70 eyes, and the results of the study showed that the AULCSF was negatively correlated with the cycloplegic NES, the total RMS Zernike coefficients, as well as the RMS Zernike coefficients for SA.…”
Section: Contrast Sensitivity Functionmentioning
confidence: 99%